The Credit Restructuring Phenomenon of The MSMEs and its Effect on Banking Financial Performance During The Pandemic of Covid-19 - Febi Rachmadi; Eko Suyono (Agregat: Jurnal Ekonomi dan Bisnis, 2021)
The purpose of this study is to analyze and explain the effect of the implementation of credit restructuring carried out by banks in the SMEs sector on the financial performance of banks during the pandemic of COVID-19 where NPL and NIM items are the intermediaries. The discussion of this paper is based on the phenomenon that is happening now where almost banking institutions conduct credit restructuring in the MSMEs sector during the pandemic of COVID-19. The results of the study explain that credit restructuring affects the performance of banks that can maintain profitability through suppressing PPAP costs, credit restructuring can reduce non-performing loans (NPL), whereas credit restructuring can reduce interest rates due to changes in accounting treatment particularly in the recognition of restructured credit interest income.